Comparative assessment of human health risk associated with heavy metals bioaccumulation in fish species (Barbus grypus and Tenualosa ilisha) from the Karoon River, Iran: Elucidating the role of habitat and feeding habits. (March 2023) - Hamidian, Amir Hossein; Sheikhzadeh, Hassan; Boujari, Azadeh; Eagderi, Soheil; Ashrafi, Sohrab
Abstract: Concentrations of Cd, Ni, and Pb were measured in the liver and muscle tissues of benthic omnivorous ( Barbus grypus ) and pelagic herbivorous ( Tenualosa ilisha ) fish collected from two sampling sites along the Karoon River, Khuzestan Province, southwest of Iran. Potential human health risks were evaluated by measuring the estimated daily intake (EDI), target hazard quotient (THQ), hazard index (HI), and target cancer risk (TR). The results highlight the important role of habitat and feeding habits in the uptake of HMs by the two species. The EDI for all HMs exceeded the oral reference doses (RfDo) provided by the USEPA, indicating the two fish species are not entirely safe for human consumption. The THQ values were within the permissible limit (< 1), while HI values (> 1) showed there was non-carcinogenic risk for consumers. The TR values for Pb were within the acceptable range (1.00E-06-1.00E-04) for both species. Highlights: HM levels were higher in benthic omnivorous than in pelagic herbivorous fish. Habitat and feeding habits played a key role in accumulation of HMs. EDI values exceeded the oral reference doses for all the HMs examined. THQ values were within and HI exceeded the permissible limits. TR values for Pb were within the acceptable range in both species.